Mechanics of aeronautical composite materials - Bouvet, Christophe (Mechanical engineering and solid mechanics series., 2017)
This book presents the principles of composite laminate sizing widely used for composite structures. The focus is on aeronautics in particular, including the concepts of limit loads and ultimate loads. After a brief overview of the main composite materials used in aeronautics, the basic theory of laminated plates and the associated rupture criteria are given. The author presents two fundamental cases of the sizing of aeronautical composite structures: the calculation of the holed structures and their subsequent multi-bolt joints, and the calculation of the buckling. The concept of damage tolerance is also explored, with a focus on its application for tolerance to impact damage. These notions are fundamental for understanding the specificities of the sizing of aeronautical composite structures. The book also contains corrected exercises for the reader to test their understanding of the different topics covered.